Design, measurement and processing of region-specific DNA methylation assays: the mass spectrometry-based method EpiTYPER - Suchiman, H. Eka D.; Slieker, Roderick C.; Kremer, Dennis; Slagboom, P. Eline; Heijmans, Bastiaan T.; Tobi, Elmar W. (Frontiers in Genetics, 2015)
EpiTYPER® is a mass spectrometry-based bisulfite sequencing method that enables region-specific DNA methylation analysis in a quantitative and high-throughput fashion. The technology targets genomic regions of 100–600 base pairs and results in the quantitative measurement of DNA methylation levels largely at single-nucleotide resolution. It is particularly suitable for larger scale efforts to study candidate regions or to validate regions from genome-wide DNA methylation studies. Here, we describe in detail how to design and perform EpiTYPER measurements and preprocess the data, providing details for high quality measurements not provided in the standard EpiTYPER protocol.